A 5-Year Prospective Multicenter Evaluation of Influenza Infection in Transplant Recipients. (7th April 2018) - Kumar, Deepali; Ferreira, Victor H; Blumberg, Emily; Silveira, Fernanda; Cordero, Elisa; Perez-Romero, Pilar; Aydillo, Teresa; Danziger-Isakov, Lara; Limaye, Ajit P; Carratala, Jordi; Munoz, Patricia; Montejo, Miguel; et al.
Abstract: Background: Seasonal influenza infection may cause significant morbidity and mortality in transplant recipients. The purpose of this study was to assess the epidemiology of symptomatic influenza infection posttransplant and determine risk factors for severe disease. Methods: Twenty centers in the United States, Canada, and Spain prospectively enrolled solid organ transplant (SOT) or hematopoietic stem cell transplant (HSCT) recipients with microbiologically confirmed inﬂuenza over 5 consecutive years (2010–2015). Demographics, microbiology data, and outcomes were collected. Serial nasopharyngeal swabs were collected at diagnosis and upto 28 days, and quantitative polymerase chain reaction for influenza A was performed. Results: We enrolled 616 patients with confirmed influenza (477 SOT; 139 HSCT). Pneumonia at presentation was in 134 of 606 (22.1%) patients. Antiviral therapy was given to 94.1% for a median of 5 days (range, 1–42 days); 66.5% patients were hospitalized and 11.0% required intensive care unit (ICU) care. The receipt of vaccine in the same influenza season was associated with a decrease in disease severity as determined by the presence of pneumonia (odds ratio [OR], 0.34 [95% confidence interval CI, .21–.55], P < .001) and ICU admission (OR, 0.49 [95% CI, .26–.90], P = .023). Similarly, early antiviral treatment (within 48 hours) was associated with improved outcomes. In patients with influenza A, pneumonia, ICU admission, and not being immunized were also associated with higher viral loads at presentation ( P = .018, P = .008, and P = .024, respectively). Conclusions: Annual influenza vaccination and early antiviral therapy are associated with a significant reduction in influenza-associated morbidity, and should be emphasized as strategies to improve outcomes of transplant recipients. Abstract : In this multicenter, multiyear, prospective, observational study of influenza infection in transplant recipients, we found that vaccination in the same season and early antiviral therapy are protective for lower respiratory tract infection and intensive care unit admission.